Seismic response of hunchbacked block type gravity quay walls - Yuksel, Z. Tugce; Yuksel, Yalcin; Cetin, K. Onder; Cevik, Esin (ELSEVIER SCI LTD, 2017)
Earthquakes near major cities may cause big social and economic impacts. Damages to port facilities may cripple the economy. The past twenty years' experience has proven the high vulnerability of the port facilities. This fact, along with the economic importance of port structures, indicates the need for better seismic design approaches for berth structures and cargo handling facilities. In the recent decades, there have been many incidences of failure of gravity type quay walls. These failures have stimulated research interest in the development of performance-based design methods. In this paper, two different hunchbacked block type quay walls with different back face shape were studied. A series of 1-g shaking tank tests was performed using a 1/10 scaled block type quay wall with gravel backfill materials on firm non-liquefiable sea bed conditions subjected to different harmonic loads. The shaking tank tests provided insight into the wall displacements and the total dynamic pressures by analyzing pressure components at the contact surface between the saturated gravel backfill soil and the wall. It is concluded that the back-face shape of the walls is an important factor and the larger positive slope of the wall improves the overall seismic stability.
Keywords: Gravity type quay wall; Block type; Seismic effects; Shaking table; Performance based design; PERFORMANCE; BEHAVIOR; CAISSON; Engineering; Geology